The midgut of Cephalotes ants (Formicidae: Myrmicinae): Ultrastructure of the epithelium and symbiotic bacteria - Bution, Murillo L.; Caetano, Flávio Henrique [UNESP] (Pergamon-Elsevier B.V. Ltd, 2010)
The ultrastructural analysis of the midgut of Cephalotes atratus. C. clypeatus, and C. pusillus reveled that the midgut epithelium lays on a basal lamina and is composed basically of three cell types: digestive cells, regenerative cells, and goblet cells. In these ants, the rough endoplasmic reticulum, in addition to producing digestive enzymes, is involved in the formation of concretions and ion storage in specialized vacuoles present in the midgut. These concretions are spherocrystals and may contribute to stabilize the pH and to maintain symbiotic bacteria found between microvilli. The ultrastructure analysis of these bacteria revealed the presence of a double envelope typical of gram-negative bacteria. For the three species examined, the ultrastructure similarities are conspicuous, suggesting that this may be the pattern for the genus Cephalotes. Details of the relationship between bacteria and microvilli were examined. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Midgut; Gram-negative bacteria; Spherocrystals; Ants